Intranasal Esthesioneuroblastoma: CT Patterns Aid in Preventing Routine Nasal Polypectomy - Peckham, M.E.; Wiggins, R.H.; Orlandi, R.R.; Anzai, Y.; Finke, W.; Harnsberger, H.R. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Esthesioneuroblastoma is a neuroectodermal tumor that commonly arises in the nasal cavity olfactory recess and, when isolated to the intranasal cavity, can be indistinguishable from benign processes. Because lesional aggressiveness requires a more invasive operation for resection than polypectomy, patients with isolated intranasal lesions were studied to define distinguishing CT characteristics.MATERIALS AND METHODS: Patients with intranasal esthesioneuroblastoma and controls without esthesioneuroblastoma with olfactory recess involvement were identified by using a report search tool. Studies demonstrating skull base invasion and/or intracranial extension were excluded. The imaging spectrum of these lesions was reviewed on both CT and MR imaging, and CT findings were compared with those of controls without esthesioneuroblastoma. Two blinded readers assessed subjects with esthesioneuroblastomas and controls without esthesioneuroblastoma and, using only CT criteria, rated their level of suspicion for esthesioneuroblastoma in each case.RESULTS: Eight histologically proved cases of intranasal esthesioneuroblastoma were reviewed. All cases had CT demonstrating 3 main findings: 1) an intranasal polypoid lesion with its epicenter in a unilateral olfactory recess, 2) causing asymmetric olfactory recess widening, and 3) extending to the cribriform plate. Twelve patients with non-esthesioneuroblastoma diseases involving the olfactory recess were used as controls. Using these 3 esthesioneuroblastoma CT criteria, 2 blinded readers evaluating patients with esthesioneuroblastoma and controls had good diagnostic accuracy (area under the curve = 0.85 for reader one, 0.81 for reader 2) for predicting esthesioneuroblastoma.CONCLUSIONS: Esthesioneuroblastoma can present as a well-marginated intranasal lesion that unilaterally widens the olfactory recess. CT patterns can help predict esthesioneuroblastoma, potentially preventing multiple operations by instigating the correct initial operative management.ENBesthesioneuroblastomaORolfactory recess